Pozycja konkurencyjna banków spółdzielczych na rynku finansowym w Polsce - Siudek, Tomasz (Competitive Position of Cooperative Banks on the Financial Market in Poland, 2006)
In this paper the author presents shares of the cooperative banks on the financial market in Poland in terms of basic bank products. The obtained results indicate that the cooperative banks have taken dominant market positions in respect of the numbers of: consumer loans, home loans, car loans, term deposits in Polish zlotys, savings books and recurring payments. On the other hand, those banks' role on the market was relatively small in respect of the number of term deposits in foreign currencies and credit cards.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 312-318